REALITY INCREASED AS A LEARNING TOOL IN CHILDREN OF SIX YEARS OF SCHOOL "JR. COLLEGE ” - López Pumalema, José Israel; Banderas Benítez, Valeria Elizabeth (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Augmented Reality, or AR, has been taking more and more force in multiple areas such as education, tourism, health, marketing, advertising, among others, thanks to the innovate way of interacting with the user. That is why we sought to investigate characteristics and components that should have an application of AR, to serve as a learning technique to the target, as well as content of greater relevance, chromatic, writing and graphic language used in the classroom by children. For this purpose, a non- experimental cross-sectional type of research was carried out, supported by surveys, test, interviews and observation of the environment. Obtaining as a result a notable improvement in the cognitive level of the children when using new TICs in the process of teaching-learning.